Corporate Responsibility - World Bank (Washington, DC, 2012)
Activists are often unhappy with the laws governing business behavior and with their enforcement. One strategy they use to alter the behavior of corporations is to target not the laws but the corporations, hoping that they will change without being legally obliged to. Sometimes firms do, because they would rather incur the costs of behaving better today than the costs of being shamed later. But how does this reputational mechanism work? Will it achieve the right standards? Which companies will it affect? And are there good reasons to prefer it to alternative ways of setting standards?